Molecular Events Involved in Influenza A Virus-Induced Cell Death - Gui, Rui; Chen, Quanjiao (Frontiers in Microbiology, 2022)
Viral infection usually leads to cell death. Moderate cell death is a protective innate immune response. By contrast, excessive, uncontrolled cell death causes tissue destruction, cytokine storm, or even host death. Thus, the struggle between the host and virus determines whether the host survives. Influenza A virus (IAV) infection in humans can lead to unbridled hyper-inflammatory reactions and cause serious illnesses and even death. A full understanding of the molecular mechanisms and regulatory networks through which IAVs induce cell death could facilitate the development of more effective antiviral treatments. In this review, we discuss current progress in research on cell death induced by IAV infection and evaluate the role of cell death in IAV replication and disease prognosis.